(untitled) (Archives of Clinical Psychiatry, 2012)
BACKGROUND: There is a strong association between good psychosocial functioning and the ability to carry out everyday tasks in patients with schizophrenia. Valid instruments become increasingly necessary to evaluate the performance of these patients in independent living activities. OBJECTIVE: To adapt and assess the psychometric properties of the Brazilian version of the Independent Living Skills Survey (ILSS-BR/P) in patients with schizophrenia. METHODS: Reliability was assessed with test-retest, interrater and internal consistency. Furthermore, construct, discriminant and concurrent validity were assessed. RESULTS: Fifty patients were included in the interrater study, with an agreement of 64.4% between responses and an Intraclass Correlation (ICC) ranged from 0.80-0.99. Forty-six patients participated in the test-retest, with an ICC ranged from 0.84-0.94 and an agreement of 44.3%. The internal consistency was good (0.23-0.98). Hundred and sixty patients participated in the validation. Regarding to the discriminant validity, female patients presented a higher performance in the overall score and five subscales compared with men. The concurrent validity confirmed the specificity of the dimensions of the scale, comparing the ILSS with the PANSS, Calgary, CGI, GAF, WHOQOL and the Rosenberg Self-Esteem. DISCUSSION: The ILSS-BR/P is a valid and reliable research instrument to assess social functioning in patients with schizophrenia.